Bricolage and assemblage as proponents for a participatory art practice through multicultural dialogue in a South African suburb - Grobler, Nicola (University of Pretoria, 2024)
Mini Dissertation (MA (Fine Arts (Creative Practice)))--University of Pretoria, 2023.